Association between types of surgery and cancer-specific death in patients with early differentiated thyroid carcinoma: a real-world study - Yu, Jia-wei; Pang, Rui; Liu, Bo; Zhang, Liang; Kong, Ling-yu (Frontiers in Oncology, 2025)
ObjectiveTo explore the association between types of surgery and outcomes in patients with early differentiated thyroid carcinoma (DTC) by a real-world study.MethodsAll the data were from Surveillance, Epidemiology, and End Results (SEER). Types of surgery included Surgery 1 (lobectomy, isthmectomy, or removal of less than a lobe), Surgery 2 (subtotal or near total thyroidectomy, or removal of a lobe and partial removal of the contralateral lobe), and Surgery 3 (total thyroidectomy). The association between types of surgery and DTC or other causes of death was explored by a competitive risk model and subgroup analysis. We also used the machine learning algorithm to evaluate the importance of types of surgery on long-term outcomes.ResultsA total of 7,230 patients were enrolled, of whom 1,512, 249, and 5,469 patients received Surgery 1, Surgery 2, and Surgery 3, respectively. The long-term outcomes among the three groups differed significantly (P < 0.001). Competitive risk analysis showed that types of surgery were significantly associated with DTC-related death (P=0.005), other causes death (P<0.001) in the crude model, and three adjusted models further indicated their independent association (all adjusted P<0.05). Specifically, Surgery 2 was associated with the highest DTC-related death. However, when the death of other causes was refined, types of surgery were only related to DTC-related death (all adjusted P<0.05). The importance analysis suggested that the impact of surgical type on long-term outcomes may be underrecognized.ConclusionsThe types of surgery were significantly related to the DTC-related death of patients, and it deserved attention. Additionally, Surgery 2 was associated with higher DTC-related death.